Nothing - Teller, Janne, 1964- (Atheneum Books for Young Readers, 2010)
When thirteen-year-old Pierre Anthon leaves school to sit in a plum tree and train for becoming part of nothing, his seventh grade classmates set out on a desperate quest for the meaning of life.